2023
DOI: 10.3389/fnut.2023.1146748
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome-modulated dietary strategies in EAE and multiple sclerosis

Abstract: Over the last few decades, the incidence of multiple sclerosis has increased as society’s dietary habits have switched from a whole foods approach to a high fat, high salt, low dietary fiber, and processed food diet, termed the “Western diet.” Environmental factors, such as diet, could play a role in the pathogenesis of multiple sclerosis due to gut microbiota alterations, gut barrier leakage, and subsequent intestinal inflammation that could lead to exacerbated neuroinflammation. This mini-review explores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…On the contrary, abnormal secretion of pro-inflammatory cytokines by T cells can lead to CNS inflammation and MS also worsens accordingly ( Kaufmann et al., 2021 ). Experimental autoimmune encephalomyelitis (EAE) is a commonly used model to study MS ( Hoffman et al., 2023 ). Study on GF mice has found that an increase in T cells and a decrease in Th1 and Th17 cell populations can alleviate EAE ( Ochs et al., 2022 ).…”
Section: Microbial Brain Gut Axis Regulates Inflammatory and Infectiv...mentioning
confidence: 99%
“…On the contrary, abnormal secretion of pro-inflammatory cytokines by T cells can lead to CNS inflammation and MS also worsens accordingly ( Kaufmann et al., 2021 ). Experimental autoimmune encephalomyelitis (EAE) is a commonly used model to study MS ( Hoffman et al., 2023 ). Study on GF mice has found that an increase in T cells and a decrease in Th1 and Th17 cell populations can alleviate EAE ( Ochs et al., 2022 ).…”
Section: Microbial Brain Gut Axis Regulates Inflammatory and Infectiv...mentioning
confidence: 99%